Sistem Informasi Manajemen Sebagai Penunjang Kinerja Operasional Industri Makanan - Muhammad Zidan Habibi; Muhammad Irwan Padli Nasution (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This article will delve deeper into how Management Information Systems (MIS) can be a key driver of operational performance in the rapidly growing food industry. In today's digital era, the food industry faces significant challenges such as global competition, rapidly changing consumer demands, and the need for continuous product innovation. Therefore, MIS has emerged as a smart solution for integrating all operational aspects, from daily data management to strategic decision-making. This research uses a qualitative approach through literature review from various trusted sources to provide an in-depth analysis of how MIS can improve efficiency, productivity, and operational competitiveness in the food sector. The results are quite interesting: MIS significantly assists in managing accurate and real-time data, integrating production and distribution processes, and even supporting product diversification, making companies more flexible. For example, through an ERP or Office Automation system, MIS can streamline operations and be more responsive to market trends. However, it's not all smooth sailing; challenges arise, such as data security issues that are vulnerable to leaks, resistance from employees unfamiliar with new technologies, and significant implementation costs. To optimize MIS, companies need to address these challenges with human resource training and a well-thought-out integration strategy. In conclusion, effective MIS implementation is crucial for driving future growth in the food industry, especially with the booming digital transformation. This article aims to provide practical insights for food industry players so they can leverage MIS to achieve a greater competitive advantage.